2011
DOI: 10.1142/s0219199711004270
|View full text |Cite
|
Sign up to set email alerts
|

Local Derivations on Algebras of Measurable Operators

Abstract: The paper is devoted to local derivations on the algebra S(M, τ) of τ -measurable operators affiliated with a von Neumann algebra M and a faithful normal semi-finite trace τ. We prove that every local derivation on S(M, τ) which is continuous in the measure topology, is in fact a derivation. In the particular case of type I von Neumann algebras, they all are inner derivations. It is proved that for type I finite von Neumann algebras without an abelian direct summand, and also for von Neumann algebras with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 12 publications
(36 reference statements)
0
36
0
Order By: Relevance
“…In this section we study local derivations on the algebra S(M, τ ) of τ -measurable operators affiliated with a von Neumann algebra M and a faithful normal semi-finite trace τ. The results presented here are due to Albeverio, Ayupov, Kudaybergenov and Nurjanov (see [7], [18]).…”
Section: Local Derivations On Algebras Of Measurable Operatorsmentioning
confidence: 80%
“…In this section we study local derivations on the algebra S(M, τ ) of τ -measurable operators affiliated with a von Neumann algebra M and a faithful normal semi-finite trace τ. The results presented here are due to Albeverio, Ayupov, Kudaybergenov and Nurjanov (see [7], [18]).…”
Section: Local Derivations On Algebras Of Measurable Operatorsmentioning
confidence: 80%
“…He also showed that every local derivation from a C * -algebra A into any Banach A-bimodule is continuous. In [4], [6] local derivations have been investigated on the algebra S(M ) of all measurable operators with respect a von Neumann algebra M . In particular, we have proved that for type I von Neumann algebras without abelian direct summands every local derivation on S(M ) is a derivation.…”
Section: A T H E M a T I C S S U B J E C T C L A S S I F I C A T I mentioning
confidence: 99%
“…In [2], we have studied local derivations on the algebra S(M, τ ) of all τ -measurable operators affiliated with a von Neumann algebra M and a faithful normal semi-finite trace τ . One of our main results in [2] (Theorem 2.1) presents an unbounded version of Kadison's Theorem A from [12], and it asserts that every local derivation on S(M, τ ) which is continuous in the measure topology automatically becomes a derivation.…”
Section: Introductionmentioning
confidence: 99%
“…One of our main results in [2] (Theorem 2.1) presents an unbounded version of Kadison's Theorem A from [12], and it asserts that every local derivation on S(M, τ ) which is continuous in the measure topology automatically becomes a derivation. In particular, for type I von Neumann algebras M all such local derivations on S(M, τ ) are inner derivations.…”
Section: Introductionmentioning
confidence: 99%